<< Chapter < Page Chapter >> Page >
                     cos ( α β ) = cos α cos β + sin α sin β                   cos ( α + β ) = ( cos α cos β sin α sin β ) ____________________________________________________ cos ( α β ) cos ( α + β ) = 2 sin α sin β

Then, we divide by 2 to isolate the product of sines:

sin α sin β = 1 2 [ cos ( α β ) cos ( α + β ) ]

Similarly we could express the product of cosines in terms of sine or derive other product-to-sum formulas.

The product-to-sum formulas

The product-to-sum formulas are as follows:

cos α cos β = 1 2 [ cos ( α β ) + cos ( α + β ) ]
sin α cos β = 1 2 [ sin ( α + β ) + sin ( α β ) ]
sin α sin β = 1 2 [ cos ( α β ) cos ( α + β ) ]
cos α sin β = 1 2 [ sin ( α + β ) sin ( α β ) ]

Express the product as a sum or difference

Write cos ( 3 θ ) cos ( 5 θ ) as a sum or difference.

We have the product of cosines, so we begin by writing the related formula. Then we substitute the given angles and simplify.

cos α cos β = 1 2 [ cos ( α β ) + cos ( α + β ) ] cos ( 3 θ ) cos ( 5 θ ) = 1 2 [ cos ( 3 θ 5 θ ) + cos ( 3 θ + 5 θ ) ] = 1 2 [ cos ( 2 θ ) + cos ( 8 θ ) ] Use even-odd identity .
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Use the product-to-sum formula to evaluate cos 11 π 12 cos π 12 .

2 3 4

Got questions? Get instant answers now!

Expressing sums as products

Some problems require the reverse of the process we just used. The sum-to-product formulas allow us to express sums of sine or cosine as products. These formulas can be derived from the product-to-sum identities. For example, with a few substitutions, we can derive the sum-to-product identity for sine . Let u + v 2 = α and u v 2 = β .

Then,

α + β = u + v 2 + u v 2 = 2 u 2 = u α β = u + v 2 u v 2 = 2 v 2 = v

Thus, replacing α and β in the product-to-sum formula with the substitute expressions, we have

sin α cos β = 1 2 [ sin ( α + β ) + sin ( α β ) ] sin ( u + v 2 ) cos ( u v 2 ) = 1 2 [ sin u + sin v ] Substitute for ( α + β )  and  ( α β ) 2 sin ( u + v 2 ) cos ( u v 2 ) = sin u + sin v

The other sum-to-product identities are derived similarly.

Sum-to-product formulas

The sum-to-product formulas are as follows:

sin α + sin β = 2 sin ( α + β 2 ) cos ( α β 2 )
sin α sin β = 2 sin ( α β 2 ) cos ( α + β 2 )
cos α cos β = −2 sin ( α + β 2 ) sin ( α β 2 )
cos α + cos β = 2 cos ( α + β 2 ) cos ( α β 2 )

Writing the difference of sines as a product

Write the following difference of sines expression as a product: sin ( 4 θ ) sin ( 2 θ ) .

We begin by writing the formula for the difference of sines.

sin α sin β = 2 sin ( α β 2 ) cos ( α + β 2 )

Substitute the values into the formula, and simplify.

sin ( 4 θ ) sin ( 2 θ ) = 2 sin ( 4 θ 2 θ 2 ) cos ( 4 θ + 2 θ 2 ) = 2 sin ( 2 θ 2 ) cos ( 6 θ 2 ) = 2 sin θ cos ( 3 θ )
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Use the sum-to-product formula to write the sum as a product: sin ( 3 θ ) + sin ( θ ) .

2 sin ( 2 θ ) cos ( θ )

Got questions? Get instant answers now!

Evaluating using the sum-to-product formula

Evaluate cos ( 15° ) cos ( 75° ) . Check the answer with a graphing calculator.

We begin by writing the formula for the difference of cosines.

cos α cos β = 2 sin ( α + β 2 ) sin ( α β 2 )

Then we substitute the given angles and simplify.

cos ( 15° ) cos ( 75° ) = −2 sin ( 15° + 75° 2 ) sin ( 15° 75° 2 ) = −2 sin ( 45° ) sin ( −30° ) = −2 ( 2 2 ) ( 1 2 ) = 2 2
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Proving an identity

Prove the identity:

cos ( 4 t ) cos ( 2 t ) sin ( 4 t ) + sin ( 2 t ) = tan t

We will start with the left side, the more complicated side of the equation, and rewrite the expression until it matches the right side.

cos ( 4 t ) cos ( 2 t ) sin ( 4 t ) + sin ( 2 t ) = 2 sin ( 4 t + 2 t 2 ) sin ( 4 t 2 t 2 ) 2 sin ( 4 t + 2 t 2 ) cos ( 4 t 2 t 2 ) = 2 sin ( 3 t ) sin t 2 sin ( 3 t ) cos t = 2 sin ( 3 t ) sin t 2 sin ( 3 t ) cos t = sin t cos t = tan t
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Questions & Answers

the gradient function of a curve is 2x+4 and the curve passes through point (1,4) find the equation of the curve
Kc Reply
1+cos²A/cos²A=2cosec²A-1
Ramesh Reply
test for convergence the series 1+x/2+2!/9x3
success Reply
a man walks up 200 meters along a straight road whose inclination is 30 degree.How high above the starting level is he?
Lhorren Reply
100 meters
Kuldeep
Find that number sum and product of all the divisors of 360
jancy Reply
answer
Ajith
exponential series
Naveen
what is subgroup
Purshotam Reply
Prove that: (2cos&+1)(2cos&-1)(2cos2&-1)=2cos4&+1
Macmillan Reply
e power cos hyperbolic (x+iy)
Vinay Reply
10y
Michael
tan hyperbolic inverse (x+iy)=alpha +i bita
Payal Reply
prove that cos(π/6-a)*cos(π/3+b)-sin(π/6-a)*sin(π/3+b)=sin(a-b)
Tejas Reply
why {2kπ} union {kπ}={kπ}?
Huy Reply
why is {2kπ} union {kπ}={kπ}? when k belong to integer
Huy
if 9 sin theta + 40 cos theta = 41,prove that:41 cos theta = 41
Trilochan Reply
what is complex numbers
Ayushi Reply
Please you teach
Dua
Yes
ahmed
Thank you
Dua
give me treganamentry question
Anshuman Reply
Solve 2cos x + 3sin x = 0.5
shobana Reply
Practice Key Terms 2

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask